Perceived mistreatment in patients with rheumatic diseases: The impact of the underlying diagnosis. - Irazú Contreras-Yáñez; Loraine Ledón-LLanes; Guillermo Arturo Guaracha-Basañez; América Sánchez-Hernández; Ana Belén Ortiz-Haro; Virginia Pascual-Ramos (PLoS ONE)
Background Mistreatment is a complex problem that impacts people's quality of life, morbidity, and mortality. In aged people, it has been associated with female sex, poor general health, depression, functional and cognitive decline, and increased dependence levels, all of which are well-recognized characteristics of patients with rheumatic diseases (RMDs). The objective was to describe the mistreatment phenomenon in Mexican patients with RMDs. We additionally report the adaptation and validation of the Geriatric Mistreatment Scale (GMS) in the target population. Patients and methods This cross-sectional study was developed in two phases (June 28, 2023-February 2, 2024), and three convenience samples were used: S-1 (n = 30), S-2 (n = 260), and S-3 (n = 372). Phase 1 consisted of adapting the GMS to RMDs (RMD-MS) (experts' agreement), followed by RMD-MS face validity (pilot testing, S-1), content validity (experts' agreement), concurrent criterion validity (family APGAR score ≤3, S-2), construct validity (exploratory factor analysis and convergent validity, S-2), reliability (internal consistency and temporal stability, S-2) and feasibility (in S-1). Phase 2 consisted of the mistreatment description in S-3. Results Patients represented typical RMD outpatients with substantial disease duration. There were 187 (50.3%) patients with overall mistreatment, and psychological was the most frequent in 142 (75.9%) patients, followed by neglect mistreatment in 96 (51.3%), sexual in 30 (16%), physical in 23 (12.3%), and economic mistreatment in 20 (10.7%) patients. Patients' perceived mistreatment was related to the underlying RMD in 13.3% of sexual mistreatment and 53.3% of psychological mistreatment. The number of "I do not want to answer" responses raised to 21.7%-67.7% for abusers' sex and 40%-72.9% for the abusers' relationship with the participant. The RMD-MS was valid, reliable, and feasible. Conclusions Half of the Mexican patients with RMDs perceived some mistreatment, most frequently psychological mistreatment, which is also often perceived as related to the underlying RMD.